Genetic evaluation of weaning weight and udder score in Nellore cattle - de Oliveira, Matheus Henrique Vargas [UNESP]; Silva, Josineudson Augusto II de Vasconcelos [UNESP]; Faria, Ricardo Antônio da Silva [UNESP]; de Paiva, José Teodoro; Malheiros, Jessica Moraes; Correia, Luiz Eduardo Cruz dos Santos [UNESP]; Albuquerque, Lucia Galvão [UNESP]; Gaya, Leila de Genova (Elsevier, 2021)
The aim of this study was to estimate genetic parameters for weaning weight (WW) and udder score (US) of 186,151 Nellore animals raised in extensive systems. The (co)variance components and estimated breeding values (EBVs) were obtained by two-trait analyses using Bayesian inference. The maternal effect (ME) was expressed as the maternal additive genetic variance of the calf's weaning weight (WW). The direct heritabilities were 0.13 ± 0.012 and 0.23 ± 0.012 for WW and US, respectively. The maternal heritability was 0.11 ± 0.012 for WW. The genetic correlations between WW and US (0.48 ± 0.053), WW and ME (0.41 ± 0.067), and US and ME (0.31 ± 0.041) were positive and moderate. Cows with maternal udder scores (US_M) 3 and 4 showed higher EBVs for ME (2.58 ± 0.070 and 2.88 ± 0.214, respectively) and their progeny had higher EBVs for WW (4.58 ± 0.058 and 5.07 ± 0.168) and US (0.20 ± 0.001 and 0.26 ± 0.005). The genetic trends demonstrate genetic progress in the selection program over the years, with values of 0.19 kg and 0.01 points for WW and US, respectively. The genetic trend in ME was 0.04 kg for WW. In addition, a positive genetic correlation was observed between these traits, as well between the traits and ME, i.e., selection would result in positive genetic gains. The use of US_M may help improve body weight and udder quality in the progeny. Furthermore, the trends indicate that the selection adopted on the farms has been effective in promoting genetic progress.
Keywords: Bayesian inference; Bos taurus indicus; Maternal effect; Selection; Variance components